2015
DOI: 10.1037/ccp0000038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic training, resistance training, or both on psychological health in adolescents with obesity: The HEARTY randomized controlled trial.

Abstract: Resistance training, alone or in combination with aerobic training, may provide psychological benefits in adolescents with overweight or obesity, and therefore could be an alternative to aerobic training for some individuals in the biological and psychological management of adolescent obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
113
2
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(132 citation statements)
references
References 50 publications
7
113
2
10
Order By: Relevance
“…Most studies reported the inclusion of a behavior modification component within the intervention. Five studies did not report the use of specific behavior change stategies . Behavior modification strategies included goal setting, problem solving, mindful eating, managing bullying and teasing, and parent role modelling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies reported the inclusion of a behavior modification component within the intervention. Five studies did not report the use of specific behavior change stategies . Behavior modification strategies included goal setting, problem solving, mindful eating, managing bullying and teasing, and parent role modelling.…”
Section: Resultsmentioning
confidence: 99%
“…The change in body image between pre‐intervention and postintervention was reported in 27 studies, between pre‐intervention and follow‐up in three studies, and 13 studies reported data at all three time points. Of the 40 studies reporting body image pre‐intervention and postintervention ranging in duration from 2 weeks to 24 months, body image was reported to be significantly improved compared with baseline in 22 studies, not significantly changed in 10 studies, five studies did not state whether or not the change was significant and three studies reported a significant improvement in one body image measure and no change in another.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also necessary to develop and utilise 378 intervention approaches to incentivise weight loss amongst those that are overweight without 379 damaging self-perception and mental health. For instance a recent physical activity 380 intervention amongst obese adolescents has shown that resistance training can achieve 381 improvements in both body image and mental health (38). …”
mentioning
confidence: 99%